On the existence of credit rationing and screening with loan size in competitive markets with imperfect information - Daniel Kraus (Universität Rostock, Institut für Volkswirtschaftslehre, 2013)
Although credit rationing has been a stylized fact since the groundbreaking papers by Stiglitz and Weiss (1981, hereinafter S-W) and Besanko and Thakor (1987a, hereinafter B-T), Arnold and Riley (2009) note that credit rationing is unlikely in the S-W model, and Clemenz (1993) shows that it does not exist in the B-T model. In this chapter, I explain why credit rationing, more specifically rationing of loan applicants, does exist in a competitive market with imperfect information, and occurs only for low-risk loan applicants. In cases of indivisible investment technologies, low-risk applicants are rationed. In cases of divisible investment technologies, rationing of loan size is restricted to rationing of loan applicants. In the event that the difference in the marginal return between the investment technologies is sufficiently small relative to the difference in their riskiness, rationing of loan size alone yields high opportunity costs; in addition, low-risk loan applicants are rationed in this case.
Keywords: G21; D82; 330; Asymmetric Information; Financial Intermediation; Credit Rationing